Manipulating rangeland soil microclimate with juniper biochar for improved native seedling establishment. Issue 3 (6th April 2021) - Phillips, Claire L.; Meyer, Kylie M.; Hanson, Chad V.; Biraud, Sébastien C.; Trippe, Kristin M.
Abstract: Encroachment of western juniper ( Juniperus occidentalis Hook.) and invasive grasses have substantially degraded sagebrush‐steppe ecosystems of the western United States. Here we evaluated whether juniper that is converted to biochar could be used in restoration seeding to improve establishment of native bunchgrasses. We hypothesized that juniper biochar could expand the window of favorable soil climate conditions for seedling establishment, either by darkening the soil surface and hastening warming in the early spring, or by enhancing soil water retention and slowing drying in the late spring. The influence of biochar application on soil albedo, temperature, and moisture were evaluated over 2 yr, along with impacts to soil fertility and establishment of bluebunch wheatgrass ( Pseudoroegneria spicata [Pursh] Á. Löve). Plots amended with biochar (14 Mg ha −1 ) were compared with plots with burn scars, where cut juniper had been piled and burned, and control plots that were areas located between burn scars where no biochar was applied. Biochar caused a small decrease in surface albedo, but no change in soil temperature or in situ soil moisture. Biochar had no impact on seedling establishment or growth over 2 yr compared with control plots. Seedling establishment was greatest in burn scars, possibly due to greater N availability. Biochar had minimal effects on soil physical and chemical characteristics, even when applied at a higher amendment rate than could be provisioned by the abundance of juniper biomass on the landscape. This trial showed juniper biochar caused no harm, but provided no clear benefits for native seedling establishment. Core Ideas: The impact of juniper biochar on bunchgrass seedling establishment was evaluated. Biochar did not improve establishment, soil moisture, or available soil nutrients. Biochar decreased albedo but did not increase surface or subsurface temperature. Seedling establishment improved on soil where juniper piles had been burned.